2022
DOI: 10.1126/sciadv.abk0445
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of a splicing program controlling neuronal excitability in flies and mammals

Abstract: Alternative splicing increases neuronal transcriptomic complexity throughout animal phylogeny. To delve into the mechanisms controlling the assembly and evolution of this regulatory layer, we characterized the neuronal microexon program in Drosophila and compared it with that of mammals. In nonvertebrate bilaterians, this splicing program is restricted to neurons by the posttranscriptional processing of the enhancer of microexons (eMIC) domain in Srrm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 85 publications
(145 reference statements)
0
17
0
Order By: Relevance
“…The coincidence of events in orthologous genes is considerably more than was detected in a similar analysis of mouse and D. melanogaster microexons ( Torres-Méndez et al 2022 ). In this study, the authors found microexons in 156 D. melanogaster genes and 2,731 mouse genes.…”
Section: Resultsmentioning
confidence: 67%
“…The coincidence of events in orthologous genes is considerably more than was detected in a similar analysis of mouse and D. melanogaster microexons ( Torres-Méndez et al 2022 ). In this study, the authors found microexons in 156 D. melanogaster genes and 2,731 mouse genes.…”
Section: Resultsmentioning
confidence: 67%
“…In Drosophila, about 15–20% of genes that undergo neuronal APA are affected at the protein‐coding level: ELAV‐mediated CDS‐APA is required for the expression of often essential neuron‐specific protein isoforms, including those of Ewg, Neuroglian, Zelda, and giant Ankyrin. One recent study particularly highlighted ELAV's direct and indirect effects on the neuronal proteome: Disruption of the ELAV‐dependent CDS‐APA of the gene Srrm234 impaired the expression of the neuron‐specific enhancer of microexons (eMIC) domain, and caused genome‐wide microexon skipping and pervasive neurological defects in flies (Torres‐Méndez et al, 2022).…”
Section: Elav‐mediated Alternative Polyadenylationmentioning
confidence: 99%
“…of the neuron-specific enhancer of microexons (eMIC) domain, and caused genome-wide microexon skipping and pervasive neurological defects in flies (Torres-Méndez et al, 2022).…”
Section: Physiological Consequences Of Loss Of Elav-mediated Apamentioning
confidence: 99%
“…By increasing genetic versatility in cells that are particularly morphologically and functionally complex, neuronal RNA isoforms are thought to contribute to the robust coordination of neuronal processes ( Hilgers, 2015 ; Miura et al., 2014 ; Pereira-Castro and Moreira, 2021 ; Turner et al., 2018 ). For example, dysregulation of neural splicing programs causes widespread neurological alterations in animal models and has been associated with human neurological conditions including autism spectrum disorder, intellectual disability, and neurodegenerative diseases ( Furlanis and Scheiffele, 2018 ; Irimia et al., 2014 ; Nik and Bowman, 2019 ; Torres-Méndez et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%